Subordinasi Kepemimpinan Perempuan dalam Budaya Batak Toba - Rispritosia Sibarani; Yurulina Gulo (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2020)
In this paper we analyze the position of women in the social life of the Toba Batak community, in influencing others to do something called a leader. In the context of such thinking, the author wants to see why women in Toba Batak have not experienced development in leadership and want to elaborate on the process of socio-cultural transmigration in Batak Bangso especially Batak Toba in political, social and cultural aspects, the majority of whose leaders are men. This paper uses a descriptive-analytic approach and with a qualitative approach. The results of the study mentioned that women experience gender inequality which is characterized by the occurrence of subordination (numbering) and marginalization of Batak women. In the field of politics, the ideal leadership is always measured from a men's perspective, so that the position of women is increasingly weak in their interaction with the surrounding community. Domestication and marginalization of women in the public sphere seems to have been exhausted and enjoyed by women because they are educated and live in a patriarchal culture by believing and believing in diverting religious teachings that are understood in a discriminatory way, and perpetuating women's alienation.